Teori Belajar Kognitif dan Implikasinya dalam Pembelajaran Bahasa Arab - Muhammad Fairuz Rosyid; R. Umi Baroroh (LP2M IAIN Sultan Amai Gorontalo, 2019)
So many number of learning theories, one of which is widely studied is cognitive theory. This article aims to examine cognitive learning theory and its implications in learning Arabic. The cognitive theory will be explored in depth based on the perspective of Jean Piaget and Lev S. Vygotsky. This article has a pattern of library research, data is explored through literature and analyzed through content analysis. The results of the analysis of this article found that cognitive theory has implications in learning Arabic in several aspects, namely: aspects of learning objectives, environmental aspects of language, aspects of media use, aspects of culture, aspects of learning levels and aspects of learning models.